LİDERLİK ALGISININ İŞ TATMİNİ ÜZERİNE ETKİLERİ: FIRAT ÜNİVERSİTESİ ÖRNEK ÇALIŞMASI - ORHAN, E. BUĞRA (Fırat Üniveristesi, 2014)
Bu çalışmanın amacı, sağlık personellerinin iş tatmini ve liderlik algısı arasındaki ilişkiyi ölçmektir. Çalışmanın birinci ve ikinci bölümünde literatür araştırması yapılmış, iş tatmini ve liderlik ile ilgili kavramlar açıklanmıştır. Çalışmanın üçüncü bölümünde araştırma yöntemi sunulmuştur. Dördüncü bölümde araştırma sonuçlarına ilişkin bilgi verilmektedir. Çalışmanın sonuç bölümünde ise araştırmanın temel bulgularına değinilerek gelecekteki araştırmalara yönelik tavsiyelerde bulunularak çalışma bitirilmektedir. Anahtar Kelimeler: İş tatmini, liderlik

The aim of this study is to measure the relationship between the job satisfaction of health workers and leadership perception of the managers in a university hospital. In the first and second chapters of the thesis a comprehensive literature research is given and the concepts related with job satisfaction and leadership are also explained. In the third chapter the methodology of the study is presented. The results are given in the fourth chapter. In the fifth or final chapter the essential findings of the study is discussed and some recommendations about the future studies on similar are presented thus ending the study. Key Words: Job satisfaction, Leadership.
The effects of leadership perception on job satisfaction : Study of Fırat University
Keywords: İşletme